Evaluation of sedative and analgesic effects of intravenous sub anesthetic doses of ketamine in horses - Cucuzella, Danielle N. (My University, 2025)
Background: Sedation and analgesia in emergency or refractory cases of pain in standing equids is of clinical importance. There are limited reports investigating the effects of administering sub-anesthetic doses of ketamine to the standing horse. Objective: To evaluate the sedative and analgesic effects of a single intravenous sub-anesthetic bolus of ketamine at two doses with detomidine as compared to a detomidine control. Study design: Prospective, blinded, placebo-controlled Methods: Monitoring of heart rate, sedation level, ataxia, procedural condition, and algometry scores of horses administered two sub-anesthetic doses of ketamine with detomidine compared to detomidine controls. Results: Eight horses were administered detomidine alone, or in combination with two sub-anesthetic doses of ketamine. A dose dependent ataxia was observed in all ketamine treated horses immediately after intravenous bolus, lasting 3-5 minutes compared to control. Horses in ketamine treated groups had an extended duration of sedation and increased threshold to stimuli in the first 8 minutes after administration when compared to control horses. Hypersalivation in 25% (4/16) ketamine treated groups, AV block in 33% (8/24) of all groups, aberrant aggression in one horse (1/8) control horses, and recumbency in one ketamine treated horse (1/16) was observed. Main limitations: The small sample size and use of non-clinically affected animals. Conclusion: Use of sub-anesthetic doses of ketamine with detomidine administered as a single, intravenous, bolus resulted in superior sedation, prolonged increase in nociceptive threshold, and a dose dependent increase in ataxia scores.
Keywords: Horse; Equine; Ketamine; Standing sedation; Sub-anesthetic